ANALISA PERSEPSI DAN HARAPAN TERHADAP KONSELING PRANIKAH PERKAWINAN - Marpaung, Halomoan; Nurmaida, Nurmaida (ANALITIKA, 2011)
This study aims to analyze the perceptions and expectations of premarital counseling. As the study sample was 70 couple. The results showed that of the indicators that are part of the five dimensions of the societal expectations of counseling before marriage, the highest expectations on religious dimensions. Â Â Â Â Â Â  By 99.5% what is expected by respondents occurred in his life after experiencing the developed relationship counseling and a balanced attitude toward the family on both sides of husband and wife. Indicator with the smallest percentage value is the dimension of integrity with a ratio of 83.25%, namely: Maintaining unity both in relationships with individuals and institutions. This means that the respondent would hope the preservation of unity in both individual and institutional relationships that exist after counseling, only 83.25% according to their perception becomes reality. The value of spearman rank correlation (rs) between perception (X) and hope (Y) is at 99., 91%. This indicated that the relationship between perceptions as independent variables is very strong in the hope (Y) as the dependent variable. Based on t test, t values obtained count equal 114.207, this value is very far when compared with the t table at â = 0.05%, thus it can be concluded that the perception variables (X) is very significant influence expectations variable (Y) as the dependent variable.